2023
DOI: 10.2147/prbm.s385413
|View full text |Cite
|
Sign up to set email alerts
|

Yoga and Mindfulness for Social-Emotional Development and Resilience in 3–5 Year-Old Children: Non-Randomized, Controlled Intervention

Abstract: Background Early childhood is the key life course period for development of social-emotional skills, providing the foundation for school readiness and resilience in later life. Age-appropriate yoga and mindfulness programs may contribute to the development of critical skills in children. Young children from minoritized communities that face structural racism and health disparities may benefit from programs that support social-emotional development and contribute to future academic success. Systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Research has indicated that engaging in yoga serves as an effective intervention in mitigating anxiety, depression, and associated symptoms or behaviors among children and adolescents [24][25][26]. For typically developing children, yoga can also promote physical and mental health [27], as well as improve emotional regulation and self-awareness [28][29][30]. The study conducted by Morena-Gomez and Cejudo on kindergarten students revealed further advantages of mindfulness-based programs, which encompassed practices such as meditation, mandalas, and body awareness activities.…”
Section: The Theory and Practice Of Group Therapymentioning
confidence: 99%
“…Research has indicated that engaging in yoga serves as an effective intervention in mitigating anxiety, depression, and associated symptoms or behaviors among children and adolescents [24][25][26]. For typically developing children, yoga can also promote physical and mental health [27], as well as improve emotional regulation and self-awareness [28][29][30]. The study conducted by Morena-Gomez and Cejudo on kindergarten students revealed further advantages of mindfulness-based programs, which encompassed practices such as meditation, mandalas, and body awareness activities.…”
Section: The Theory and Practice Of Group Therapymentioning
confidence: 99%